Platelet recruitment kinetics are impacted by von Willebrand factor quality in hemostatic adjuncts - Kimberly A. Thomas; Alice Liu; David L. Bark, Jr.; Philip C. Spinella; Susan M. Shea (Blood Vessels, Thrombosis & Hemostasis)
Abstract: Traumatic injury has the highest burden on morbidity and mortality in the United States. Early deaths from trauma are most frequently due to hemorrhage and could be prevented with more timely and efficacious treatments. A hallmark of trauma-induced coagulopathy (TIC) is hypofibrinogenemia, which is treated with fibrinogen concentrates (FibCon) or cryoprecipitate (Cryo). Pathogen reduction (PR) of Cryo (PR-CryoFC) enables extended storage after thaw at room temperature, permitting immediate availability for patients with bleeding. As Cryo contains additional concentrated plasma proteins involved in hemostasis compared with FibCon, we hypothesized that Cryo and PR-CryoFC would result in more rapid and effective clot formation. To evaluate the hemostatic capacity of these adjuncts, we simulated TIC (dilution, hyperfibrinolysis) in an ex vivo model and administered Cryo, PR-CryoFC, and FibCon, then performed hemostatic assessment to include viscoelastometry, thrombin generation, and a microfluidic model of vessel injury. Cryo and PR-CryoFC had similar resuscitation capacity in assays without flow (viscoelastometry, thrombin generation), whereas in the dynamic microfluidic model, Cryo had faster von Willebrand factor (VWF)-mediated platelet recruitment. There was no difference in intrinsic VWF function between adjuncts in static, nonflowing assays, yet in a flow-dependent vortexing assay, PR reduced VWF cleavage by ADAMTS13, despite equivalent ADAMTS13 activity, suggesting impaired biophysical elongation and extension of VWF in PR-CryoFC, resulting in reduced cleavage and platelet binding capacity. Herein, we show ex vivo simulation of coagulopathy and resuscitation differentiated hemostatic function under flow among Cryo, PR-CryoFC, and FibCon. Further exploration of effects of PR on plasma proteins is warranted as well as effects on clinical outcomes.